ʿUbaid-related sites of the southern Gulf revisited: the Abu Dhabi Coastal Heritage Initiative - Beech, Mark Jonathan; Strutt, Kristian; Blue, Lucy; Al Kaabi, Abdulla Khalfan; Omar, Waleed Awad; Al Haj El Faki, Ahmed Abdulla; Lingareddy, Anjana Reddy; Martin, John (Proceedings of the Seminar for Arabian Studies, 2016)
The Coastal Heritage Initiative of the Abu Dhabi Tourism and Culture Authority (TCA Abu Dhabi) aims to investigate the rich maritime history of Abu Dhabi Emirate. Since the establishment of TCA Abu Dhabi in February 2012, a new phase of archaeological research has been carried out. Systematic mapping of sites, their integration into the Abu Dhabi geographic information system (GIS geodatabase of archaeological sites for the Emirate), as well as further investigations of key sites by both geophysical prospection and excavation have been undertaken. Recent work has concentrated on the ʿUbaid-related coastal sites on both Dalma Island (Jazīrat Dalmā) and Marawah Island (Jazīrat Marawaḥ). A combination of both magnetometry and ground-penetrating radar (GPR) geophysical surveys, as well as follow-up excavations are discussed. These shed new light on the structure of ʿUbaid-related coastal settlements between the mid-sixth and early fifth millennium BC.